0911 Association Between Chromosomal Abnormality And Sleep Disordered Breathing Characteristics In Children With Prader Willi Syndrome. (27th May 2020) - Gupta, G; Veeravigrom, M; Felt, B; O'Brien, L
Abstract: Introduction: Prader-Willi Syndrome (PWS) is a genetic disorder caused by lack of expression of paternal genes from the chromosomal region 15 q11.2-q13. PWS is associated with excessive daytime sleepiness, sleep-disordered breathing (SDB), hypoventilation and circadian rhythm disturbance. Chromosomal deletion and uniparental disomy (UPD) are the two most common genetic etiologies of PWS. Differences in clinical features between these groups are recognized; however, limited literature exists regarding sleep characteristics. Methods: The objective was to evaluate sleep characteristics of children with PWS between those with 15q11.2-q13 chromosomal deletion and those with other genetic etiologies. A retrospective chart review of in-laboratory polysomnograms (PSG) in children with PWS prior to growth hormone treatment was performed. The apnea hypopnea index (AHI), REM AHI, NREM AHI, Obstructive Apnea Index (OAI), Central Apnea Index (CAI), hypopnea index, arousal index, presence of hypoventilation, and positional AHI were assessed. Results: Overall 33 PWS children were identified. Mean age was 5.9 ± 5.19 (range 1-16 years), 57% were male and 85% had SDB. Almost half (42%) had a 15q11.2-q13 chromosomal deletion. Of those without deletion, 30% had UPD. Sleep variables were similar in PWS with and without deletion: AHI (5.9±5.7 vs. 8.54±7.1; p=0.27), NREM AHI (3.3±4.6 vs. 6.2±6.3; p=0.16), CAI (1.1±1.5 vs. 1.9±3.8; p=0.43) SpO2 nadir 82.7±9.9% vs. 85.3±5.7%; p=0.36) and arousal index (10.3±7.8 vs. 15.4±7.8; p=0.09). Conclusion: Sleep characteristics do not appear to clearly differ between genetic etiologies of PWS. Larger sample sizes are needed to support these findings. Support: